Building an instrument for assessing the environmental perception associated with the environmental impacts of daily actions - Beckmann, Lilian Janine de Barros (2021)
In recent years, environmental degradation has intensified and the finitude of natural resources has become more evident. Economic and technological development is not always in harmony with the environment, generating a series of environmental damages that need to be understood and admitted. This work addresses the construction of an instrument to assess the perception of the environmental impact of individuals' daily activities. A questionnaire was prepared to assess the perception of environmental impact related to the aspects of food, housing, transportation, water consumption, electricity consumption, and clothing purchase. Afterwards, the questionnaire validation process was carried out, which resulted in a descriptive question and fourteen objective questions about how the various daily activities can impact the environment on a Likert scale from 1 to 10. The questionnaire was applied to students of an undergraduate course and the results pointed out internal coherence, registering as main recognized impacts: the production of garbage, waste of water and light, and air pollution. The instrument for assessing the environmental impact of everyday actions is a tool that can be used in the school context to address issues related to the environmental issue to promote a discussion on the environmental impacts produced by our individual actions; and it can also be used for the evaluation of pedagogical activities related to Environmental Education through the application before and after the application of these activities.